Muslim societies : historical and comparative aspects - Tsugitaka, Sato (New horizons in Islamic studies., 2004)
This volume examines Muslim societies across Europe, North Africa, Central Asia and South Asia from the eighteenth century to the present, providing fresh insight through comparison.